The Effectiveness of Special Relativity Student Worksheet Assisted by The Pythagorean Theorem in Physics Learning - Bambang Supriadi; Sakti Kalisa Sefanda; Badriyah Badriyah; Fidia Alhikmah Putri; Ummi Zahrotul Ainiyah; Habibah Khusna Baihaq; Muhammad Najih Hamdi (Jurnal Pendidikan Fisika Indonesia, 2026)
In the 21st-century education era, integrating innovative learning media is essential to develop mathematical thinking skills and improve overall student learning outcomes, especially when addressing highly abstract physics topics such as Einstein’s special theory of relativity. This research aims to implement a specifically designed Student Worksheet (SW) assisted by the Pythagoras theorem to develop mathematical thinking indicators, enhance student learning performance, and evaluate student responses toward the media. The research employed a pre-experimental method with a one-group pretest-posttest design conducted at SMAN Mumbulsari during the 2024/2025 academic year. Using convenience sampling, 72 eleventh-grade students from two physics elective classes were selected as research subjects. Data collection was carried out using validated pretest-posttest essay questions, Student Worksheets focused on four key mathematical thinking elements: specializing, generalizing, conjecturing, and convincing, and response questionnaires based on a Likert scale. Data analysis utilized the Normalized Gain (N-gain) score to measure the improvement in learning outcomes and descriptive statistics to determine the percentage of student responses. The results indicated that students' mathematical thinking skills fell into the good to very good range across all indicators. Furthermore, learning outcomes showed an average N-gain of 0.57, placing the improvement in the moderate category, complemented by a positive student response rate of 68.20%. These findings demonstrate that the Pythagoras-assisted SW effectively improves learning performance in physics. This research provides significant practical benefits as an innovative instructional alternative for physics teachers, simplifying complex, abstract concepts through a geometric approach, thereby helping students overcome mathematical barriers and fostering a deeper understanding of physics.